PENGUJIAN KEMBALI TEORI PECKING ORDER DAN TRADE-OFF PADA PERUSAHAAN TUMBUH DAN DEWASA DI BURSA EFEK INDONESIA - , MAYA BELIYA, Prof. Dr. Eduardus Tandelilin, M.B.A. CWM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Each company has different capital structure which is coming from variate financial source, either external or internal. Pecking order theory and static trade-off theory are theory of capital structure that can be used to analize companies debt. Companies with different state and growth rate, correspondingly have different financial decision to be applied. Growth company, which is still a new company requires greater financing mature company in resources and capital cost. This study was conducted to analize the use of pecking order theory in preparation of capital structure of growth company and the use of static trade-off theory in preparation of capital structure of mature company at Indonesian Capital Market started from 2007 to 2011. The pecking order model generally able to explain the growth company's capital structure decision in Indonesia. The extended pecking order model which is derived from pecking order model simultaneously explains a significant impact on the company's long-term debt issuance. While the trade-off theory model has not yet concluded to be used by mature company, even in mature companies there is an indication of financial decision which support the pecking order theory.